PENERAPAN MODEL PEMBELAJARAN READ, ANSWER, DISCUSS, EXPLAIN AND CREATE (RADEC) UNTUK MENINGKATKAN CIVIC KNOWLEDGE PADA PEMBELAJARAN PENDIDIKAN PANCASILA SISWA SEKOLAH DASAR - Samidah; Mufarizuddin; Fitra Surya, Yenni; Ananda, Rizki; Indra Daulay, Musnar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low civic knowledge of students in learning Pancasila education in class V UPT SDN 017 Laggini. One solution to overcome this problem is to use the Read, Answer, Discuss, Explain and Create (RADEC) learning model for class V students at UPT SDN 017 Laggini. This research method is Classroom Action Research (PTK) which is carried out in two cycles consisting of 2 meetings and four stages, namely planning, implementation, observation and reflection. When this research was carried out in July 2024. The subjects of this research were 12 class V students of UPT SDN 017 Laggini. Consists of 4 male students and 8 female students. Data collection methods use tests, observation and documentation. The results of this research can be concluded that students' civic knowledge abilities have increased in each cycle, where the percentage results in cycle I, meeting I (33%), meeting II increased to (42%), while in cycle II, meeting I (58%) and meeting II increased to (83%). Thus, it can be concluded that by implementing the Read, Answer, Discuss, Explain and Create (RADEC) learning model, it can increase civic knowledge in class V students at UPT SDN 017 Laggini.